Traumatic Experiences Depicted in Colleen Hoover’s Hopeless - Ardhella Nuritamaya; Anita Sari (Morphosis: Journal of Literature, 2024)
This research aims to analyze traumatic experience depicted in a contemporary literary work. The object of this study are the traumatic events experienced by the main character from a novel entitled Hopeless (2013) by Colleen Hoover. This study applies a qualitative research method as the analysis is presented in the form of textual interpretation which utilizes narrative type of research design as the discussion mainly explored the life experience of a character in the novel. The writer uses the concept of trauma and memory proposed by Cathy Caruth (1995) as the conceptual guidance in this study. The study found that the traumatic responses reflected from Sky’s attitude are the intrusion, avoidance, and negative alterations of cognition and mood symptoms. The avoidance symptoms are the most prominent and/or dominant symptom that Sky is experiencing throughout her life. The results of the study stated that there were two types of indicators of the impact of trauma on her psyche which were contradictory that emerge from repeated and prolonged traumatic experience: Sky is amnestic for the early life she had during her childhood; while she simultaneously remembers too much of the traumatic event in terms of how it influences her life as an adolescent. Keywords: dissociative memory, psychological impact, traumatic experience, traumatic symptoms